Efeito da temperatura sobre a expressão de fatores miogênicos no músculo estriado esquelético do pacu (Piaractus mesopotamicus) - Paula, Tassiana Gutierrez de [UNESP] (2013)
Muscle growth in teleost fish involves the balance between the recruitment (hyperplasia) and the enlargement (hypertrophy) of muscle fibers, mechanisms that are controlled by many transcription factors, as the MyoD family and growth factors as myostatin. Several environmental factors such as temperature can influence the muscle fiber cellularity, and the expression of genes related with muscle development and growth, affecting the growth rate pattern in fish. Pacu is a fast growing fish extensively used in Brazilian aquaculture programs and shows a wide range of thermal tolerance. As temperature is an environmental factor that influences the fish growth rate, parameter directly related with muscle plasticity and growth, we hypothesized that different rearing temperatures in juvenile of pacu, which presents an intense muscle growth by hyperplasia, can potentially alter the muscle cellularity that could influence the muscle growth patterns in this species. The aim of this study is to analyze the muscle growth characteristics and the expression of Myogenic Regulatory Factors, MyoD and myogenin, and the growth factor myostatin in juvenile of pacu (Piaractus mesopotamicus) submitted to the different rearing temperatures. Juvenile fish (1.5 g weight) were distributed in tanks containing water and maintained at 24 (G24), 28 (G28) and 32 (G32)°C (three replicates for each group) during 60 days. At days 30 and 60, fish were anesthetized, euthanized and muscle samples (n=12) were collected for morphological, morphometric and gene expression analyses. At days 30, the body weight and the standard length were lower in fish reared at 24 °C. Muscle fiber frequency in the class <25μm was significantly higher in fish reared at 24 °C, compared to the fish reared at 28 and 32 °C. Considering the frequency distribution of muscle fiber diameter in the class >50 μm, fish reared at 28 and 32 ºC showed similar result and these was higher than that ...